Treatment of patients with complicated fractures of the distal humerus using the fixators of limited-contact multiplanar osteosynthesis - Bilinskyi, Petro (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2021)
Treatment of distal humerus fractures is a complex problem in traumatology. The result of treatment depends on the choice of fixator according to the fracture area. Objective. To improve the technology of treatment in patients with complicated distal humerus fractures with fixators of small contact and multiplanar osteosynthesis and to evaluate its efficacy. Methods. 39 patients were treated for the period 2000–2020 with distal humerus nonunion (types 12-B1, 12-C1, 12-C2) and 23 patients with complicated above- and transcondylar humerus fractures (types 13-A2, 13-C1, 13-C2). Fixation of bone fragments of the distal humerus was made with device for fixation (Patent 17502 UA). It is a shaped plate with a groove on which half rings with threaded holes are stabilized. For the osteosynthesis of above- and transcondylar humerus fractures we used V-shaped plate with the possibility to regulate branch spreading width as for the condylar size (Patent 33358 UA). Autografting was performed as for necessity. Results. Plate osteosynthesis was performed mainly through anterior approach with minimal tissues traumatization. Release of radial nerve we made as for necessity. This device provides the stable fixation even in a case of short distal fragment. Device for bone fragments fixation was placed on the posterior condylar surface and lower part of the humerus through olecranon osteotomy. Osteosynthesis with suggested device is one of the options with bone autografting and can be method of choice at repeated surgery. Follow-up period was 1–2 years and later. In 60 patients we obtained good results with completed bone union. Conclusions. Suggested device can be used in cases of distal humerus nonunion. It allows to decrease the damage of surgery, to avoid many complications. Key words. Complicated fractures of the distal humerus, devices for limited-contact multiplanar osteosynthesis.